World checklist of Moltkia (Boraginaceae) with notes on types - Ranjbar, Massoud; Khalvati, Sina (Phytotaxa, 2019)
An updated checklist of the genus Moltkia is presented and seven taxa (six species and one subspecies) are recognized from the entire world. In this checklist, the effective place of publication of the accepted names, formal taxonomic status, nomenclature, homotypic and non-homotypic synonyms are identified and verified. Lectotypes are here designated for five names. An identification key, illustrations and a distribution map for Moltkia species are provided.